Modulation of penile erection in rabbits by mondia whitei: Possible mechanism of action - Quasie, O.; Martey, O.N.K.; Nyarko, A.K.; Gbewonyo, W.S.K.; Okine, L.K.N. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Mondia whitei root was evaluated to validate its anecdotal use and determine its possible mode of action in the management of erectile dysfunction. Rabbits were administered with daily oral doses of 100–400 mg kg−1 crude ethanolic extract of M. whitei and sildenafil (50 mg kg−1) as positive control for 6 weeks. Cavernosal tissue NOS activity and levels of NO and cGMP, and NOS and PDE protein expressions were investigated. The effect of the crude extract, chloroform and petroleum ether fractions in vitro on cavernosal tissue NOS activity and levels of NO and cGMP at 0.01 and 0.10 mg g−1 tissue were also investigated. Results indicate that the crude extract increased NOS activity by 7% at 200 mg kg−1 with corresponding increases in NO (88%) and cGMP (480%) levels. No significant changes in these measurements were observed with the 100 and 400 mg kg−1 doses whilst sildenafil slightly reduced them (15.9–37.5%). NOS and PDE protein expressions in test animals were not different from controls. Pre-incubation of cavernosal tissue in vitro with the crude extract of M. whitei and its chloroform fraction markedly increased NOS activity (26–132%) and levels of NO (25%) and cGMP (50–400%) at 0.01 mg g−1 tissue but these were reduced to near control levels when their concentrations were increased to 0.10 mg g−1 tissue whilst the petroleum ether fraction had no effect. These findings suggest that M. whitei may influence erectile function through activation/stimulation of NOS with corresponding increases in tissue NO and cGMP levels and that certain chemical constituents present in the chloroform fraction may be responsible for biological activity.
Keywords: Erectile dysfunction; Nitric oxide; cGMP; Sildenafil; Organic fractions